Blockchain Beyond Bitcoin. - Underwood, Sarah (Communications of the ACM, 2016)
The article discusses the potential application of blockchain technology, also known as distributed ledger technology, in cryptocurrencies such as Bitcoin and other fields. Topics include the cost and time efficiency of blockchain technology by eliminating a third party middleman between companies and individuals, the transparency of blockchain technology as it can by viewed by all users on a network, and the use of cryptographic algorithms to make transactions secure, auditable, and immutable.